Peculiarities of classification of purchasing, storage, transportation and processing of timber known to be illegally harvested, for the purpose of illegal sale (article 191.1 of the Criminal Code of Russia) - Ayupova, Gul'naz Shamilovna (Полицейская и следственная деятельность, 2021)
The research object is social relations in the field of legal regulation of the composition of a crime carrying responsibility for purchasing, storage, transportation, processing for the purpose of illegal sale, and illegal sale of timber known to be illegally harvested, according to the article 191.1 of the Criminal Code of Russia. The research subject is Russia's legislation imposing responsibility for the sales of illegally harvested timber, the materials of judicial practice, and theoretical views of scholars. The research methodology is based on the general dialectical method. The author also uses such research methods as logical, formal-legal, and teleological ones. The research is based on both general scientific and specific methods of scientific cognition. The purpose of the research is to formulate the proposals about the improvement of the practice of application of the article 191.1 of the Criminal Code of Russia. The scientific novelty of the research is determined by the fact that it contains theoretical provisions about the improvement and application of the article 191.1 of the Criminal Code. Particularly, the author describes the contents of particular constituent elements of this offence, including the evaluative and blanket ones, and formulates the proposals about the classification of crimes described in the article 191.1 of the Criminal Code. The author arrives at the conclusion that a crime, described in the article 191.1, is a new form of involvement in a crime, and the predicate deed is illegal harvesting of timber (article 260 of the Criminal Code, part 1 and 2 of article 8.28 of the Administrative Offences Code).